MENGKRITIK TUDINGAN ABAD KE-14 HIJRIYAH TENTANG SUMBER AL-QURAN MELALUI KITAB ULUMUL QURAN KONTEMPORER - Muhammad (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2023)
This study aims to identify some of the suspicions of the fourteenth century AH about the authenticity of the Qur’an, which come from the tongue of atheists and orientalists, and criticizing them through the books of contemporary Qur’anic studies. This study used the critical and analytical method, so the study will look at the value of these suspicions and the extent to which contemporary Quranic study books are concerned with these issues. This study, after analysis, installation and evaluation, concluded that the suspicions of the fourteenth century AH have no strong scientific value, but were invalidated by scientists with convincing and satisfactory arguments based on mental, transmission and historical evidence.